Una propuesta educativa para atender la diversidad en el contexto de aula - Agüero Agüero, Rosario (2007)
At the present time, schools face a big challenge: providing their students an education of quality and an education for everyone, in other words, an education thought for diversity within the classroom. The goal of this project is to improve the respect for the students` individual differences and make sure that diversity could be applied in to the school context. Based in a diagnostic process developed at the “Escuela Mixta San Juan”, it was found that most students show rejection and disrespect at the individual differences from many point of view. Authors such as Meléndez (2002), Parcerisa (2000), Olivé (1999) and Aguilar (2000) were revised and they provided some guides to be use at schools in order to deal with the students` diversity. These authors propose that a change of attitude and several different social transformations are required in order to warrant that diversity is appropriately taken care of. As an answer to this situation, a series of workshops and didactic activities designed to improve the cooperative knowledge production and mutual work are proposed. The proposal is based on a socio-constructivist and inclusive approach, since it attempts to respond to the students` needs within their own context. The most important aspects of diversity were taken into account, such as internal and external aspects related to the individuals. As a final goal, students are expected to express attitudes of respect toward diversity, respond to their classmates and their own educational needs, as well as show and open, critical and flexible attitude to themselves and their environment. Therefore, future generation’s education must include these skills and abilities, in order to allow them to comprehend this world as an open window to individual and collective improvement.